Evaluación de la producción del pasto king grass (pennisetum purpureum x pennisetum thiphoides con abonos orgánicos sólidos - Tituaña Alcaciega, Isidro Rodrigo (2012)
This research work was carried out between May and August, during 2011, on the farm "San Carlos", located at Km 28 via Quevedo - Santo Domingo, whose geographical coordinates are 79 ° 29 ' west longitude and 0 ° 52 'South latitude at an altitude de120msnm. The investigation lasted 90 days. Raised the overall objective: To evaluate the behavior of King grass (Pennisetum purpureum x Pennisetum thiphoides) with solid organic fertilizers and specific: a) Determine the agronomic performance of grass with compost King grass b) Analyze the nutritional value of grass study by Chemical analyzes c) Establish the cost benefit of the treatments under study. Subject to the assumptions: a) Treatment with a cutoff age of 75 days concentration of organic fertilizer (1500 kg ha-1) will provide greater vegetative growth in the cultivation of King grass; b) One of the treatments present a lower production cost c) Treatment with a cutoff age of 30 days concentration of organic fertilizer (1500 kg ha-1) present the best chemical composition. Forage Biomass yields Verde (MV kg ha-1), Forage Dry Biomass (kg DM ha-1), plant height, leaf and stem weight (g), leaf length and width of leaves were significantly affected by cutting ages, increasing to over harvest ages, accounting for the age cutoff at 75 days, higher production yields. The use of solid manure AGROPESA, induced a higher yield of biomass and biomass Fodder Green Fodder Dry, compared with the control at 30, 45, 60 and 75 days. The higher yields for the grass King grass, was presented by treatment with 1500 kg ha-1 compost AGROPESA and an age cutoff of 75 days, with a production of green matter 74400.00 kg ha-1 and performance dry matter 19329.12 kg ha-1. The protein content increased in the grass by using King grass fertilizer levels, presenting the highest protein content with the use of 1500 kg ha-1 compost and a cutoff age of 75 days to get the 9.46 %.